2007
DOI: 10.1158/0008-5472.can-06-4490
|View full text |Cite
|
Sign up to set email alerts
|

RAD001 (Everolimus) Delays Tumor Onset and Progression in a Transgenic Mouse Model of Ovarian Cancer

Abstract: The mammalian target of rapamycin (mTOR) is thought to play a critical role in regulating cell growth, cell cycle progression, and tumorigenesis. Because the AKT-mTOR pathway is frequently hyperactivated in ovarian cancer, we hypothesized that the mTOR inhibitor RAD001 (Everolimus) would inhibit ovarian tumorigenesis in transgenic mice that spontaneously develop ovarian carcinomas. We used TgMISIIR-TAg transgenic mice, which develop bilateral ovarian serous adenocarcinomas accompanied by ascites and peritoneal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(152 citation statements)
references
References 19 publications
9
142
0
1
Order By: Relevance
“…Longitudinal MRI was also used to accurately measure ovarian tumor size and response to treatment with RAD001 (Everolimus) showing that tumor onset and progression was significantly delayed in treated versus control mice. 23 Taken together, our results suggest that TgMISIIR-TAg-DR26 transgenic mice may be a useful model for the preclinical evaluation of novel combination therapies for the treatment of EOC.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Longitudinal MRI was also used to accurately measure ovarian tumor size and response to treatment with RAD001 (Everolimus) showing that tumor onset and progression was significantly delayed in treated versus control mice. 23 Taken together, our results suggest that TgMISIIR-TAg-DR26 transgenic mice may be a useful model for the preclinical evaluation of novel combination therapies for the treatment of EOC.…”
Section: Discussionsupporting
confidence: 52%
“…We conducted a preclinical study of the therapeutic efficacy of RAD001 (Everolimus) in TgMISIIR-TAg-DR26 mice and showed that this single agent significantly delays tumor onset and progression in the mice. 23 The availability of reliable and accurate methods for in vivo imaging of normal ovaries and ovarian tumors provides the opportunity to fully characterize tumor growth kinetics, disease progression and therapeutic response. These analyses provide the information necessary to optimize preclinical studies so they can be conducted using fewer mice and longitudinal quantitative data is obtained for each mouse.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] In particular, five MMTV-c-Neu mice bearing tumors were treated with 150 g rapamycin (a dose approximately 3 times higher than the dose used in our study) for 32 days and tumor regression was observed. 29 However, the effect of rapamycin on longevity of cancer-prone mice has not been previously investigated.…”
Section: Discussionmentioning
confidence: 89%
“…The disease in hens appears to closely resemble the human disease, which in humans is correlated with ovulation frequency [6]. Whereas there are important rodent models for epithelial ovarian cancer, none of these ovarian carcinomas are linked to ovulation [7][8][9][10][11][12][13]. One of the most prevalent theories about the etiology of ovarian cancer is the "incessant ovulation hypothesis" first proposed by Fathalla [14].…”
Section: Introductionmentioning
confidence: 99%